2023
DOI: 10.21468/scipostphys.14.5.113
|View full text |Cite
|
Sign up to set email alerts
|

Loop current fluctuations and quantum critical transport

Abstract: We study electrical transport at quantum critical points (QCPs) associated with loop current ordering in a metal, focusing specifically on models of the “Hertz-Millis” type. At the infrared (IR) fixed point and in the absence of disorder, the simplest such models have infinite DC conductivity and zero incoherent conductivity at nonzero frequencies. However, we find that a particular deformation, involving NN species of bosons and fermions with random couplings in flavor space, admits a finite incoherent, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The mechanism in the work of Shi et al . ( 22 ) for the noncommutativity of the large N and small ω limits applies only for order parameters with the same symmetry as the momentum in the spatially uniform case and does not apply for the spatially disordered case, which has no conserved momentum and for which the patches do not decouple.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism in the work of Shi et al . ( 22 ) for the noncommutativity of the large N and small ω limits applies only for order parameters with the same symmetry as the momentum in the spatially uniform case and does not apply for the spatially disordered case, which has no conserved momentum and for which the patches do not decouple.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The large N computation of the conductivity ( 17 , 22 ) yields only the clean Drude result Reσω/N=πNvF2δω/2, where N=m/2π is the fermion density of states at the Fermi level. This is in contrast to the results of previous studies ( 12 , 40 ), in which it has been found that dc resistivity is ~ T 4/3 and optical conductivity is ω2/3.…”
Section: Spatially Uniform Quantum Critical Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing issue concerns the application of our criterion to theories of quantum-critical metals, especially in cases where the electrical resistivity is T − linear 27 , 61 , 62 . In this regard, we point out ref.…”
Section: Discussionmentioning
confidence: 99%